Expanding the Independent Global Stocktake Hub in West Africa for inclusive climate action - Hackman, O Kwame; Gandji, Kisito; Ouedraogo, Ramata; Segnon, Alcade Christel; Salack, Seyni; Zougmore, Robert Bellarmin (2025)
Agreement in West Africa is the limited participation of civil society due to weak engagement mechanisms, fragmented networks, and insufficient capacity to inform NDC processes. The iGST West Africa Regional Hub seeks to fill this gap by uniting over 500 climate-focused organizations to strengthen civil society engagement, build capacity, and promote inclusive, evidence-based climate action and policymaking across the region. Expanding the Hub’s coverage in West Africa is essential to enhance its reach, foster collaboration with governments, and promote inclusive participation in climate action and policymaking. Thanks to AICCRA support, the Hub has been expanded to two additional countries (Togo and Côte d’Ivoire) while maintaining active engagement in existing networks, including Ghana, Mali, and Senegal. Through the Hub, AICCRA extends its partnership with civil society across West Africa, creating opportunities to scale CSA technologies and services in the region.